2007
DOI: 10.1002/hep.21930
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study of extracorporeal albumin dialysis for hepatic encephalopathy in advanced cirrhosis

Abstract: Extracorporeal albumin dialysis (ECAD) may improve severe hepatic encephalopathy (HE) in patients with advanced cirrhosis via the removal of protein or non-protein-bound toxins. A prospective, randomized, controlled, multicenter trial of the efficacy, safety, and tolerability of ECAD using molecular adsorbent recirculating system (MARS) was conducted in such patients. Patients were randomized to ECAD and standard medical therapy (SMT) or SMT alone. ECAD was provided daily for 6 hours for 5 days or until the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
204
1
18

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(236 citation statements)
references
References 26 publications
13
204
1
18
Order By: Relevance
“…4,[10][11][12] Current hypotheses suggest that the removal of excess protein-bound toxins in the extracorporeal circuit is likely to regenerate the native albumin, thereby enhancing its functional capacity so that it may be able to transport and detoxify more toxins. Contrary to this existing hypothesis, albumin dialysis using MARS did not improve the measured functional capacity of the patient's circulating albumin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[10][11][12] Current hypotheses suggest that the removal of excess protein-bound toxins in the extracorporeal circuit is likely to regenerate the native albumin, thereby enhancing its functional capacity so that it may be able to transport and detoxify more toxins. Contrary to this existing hypothesis, albumin dialysis using MARS did not improve the measured functional capacity of the patient's circulating albumin.…”
Section: Discussionmentioning
confidence: 99%
“…One such device that is commercially available is the Molecular Adsorbents Recirculating System (MARS) (Gambro, Lund, Sweden) and studies using this device show beneficial pathophysiological and clinical effects particularly in reducing the severity of hepatic encephalopathy with small studies also showing possible survival benefit in liver failure patients. [10][11][12] However, at present, detailed functional characteristics of the different binding sites in cirrhosis have not been determined. The overall aim of this study was to perform a detailed qualitative and quantitative assessment of the functional capacity of albumin in patients with liver disease of varying severities and to determine whether these alterations could be used as a marker of disease severity and prognosis.…”
mentioning
confidence: 99%
“…However, significant differences in survival were found at day 90 (albumin 69.2% versus saline 40.0%; P = 0.02) suggesting that the development of HE may identify a subgroup of patients with advanced cirrhosis that may benefit from the administration of albumin. 114 Albumin dialysis has also been studied in a randomized controlled trial in patients with HE and advanced cirrhosis, and found to be effective for the treatment of HE, 115 however the benefits of albumin dialysis appear to be independent of changes in ammonia level or cytokines. 116 An albumin replacement system with a novel endotoxin ligation (ARSeNEL) component has been developed and tested in a porcine ALF model.…”
Section: Human Albumin Solutionmentioning
confidence: 99%
“…44 Currently, the Molecular Adsorbent Recirculating System (MARS ® ) is the only extracorporeal liver support device that has proven to be effective in improving severe (grade 3 and 4) hepatic encephalopathy by a prospective randomized multi-center study. 45 In short, patients with end stage chronic liver disease (MELD score around 30, CTP score above 10) and intractable severe coma (HE grade 3 and 4, Glasgow Coma Scale around 7) who did not respond to prior conventional therapy were randomized to either additional daily MARS ® therapy or continuation of standard therapy only.…”
Section: Clinical Resultsmentioning
confidence: 99%